Determination of flow resistance coefficient for vegetation in open channel: laboratory study - Ahmad, Noor Aliza; Md Ali, Zarina; Mohd Arish, Nur Aini; Mat Daud, Azra Munirah (IOP Publishing, 2018)
This study focused on determination of flow resistances coefficient for grass in an open channel. Laboratory works were conducted to examine the effects of varying of roughness elements on the flume to determine flow resistance coefficient and also to determine the optimum flow resistance with five different flow rate, Q. Laboratory study with two type of vegetation which are Cow Grass and Pearl Grass were implementing to the bed of a flume. The roughness coefficient, n value is determine using Manning’s equation while Soil Conservation Services (SCS) method was used to determine the surface resistance. From the experiment, the flow resistance coefficient for Cow Grass in range 0.0008 - 0.0039 while Pearl Grass value for the flow resistance coefficient are in between 0.0013 - 0.0054. As a conclusion the vegetation roughness value in open channel are depends on density, distribution type of vegetation used and physical characteristic of the vegetation itself